(3GSJQGJjLjI GdJOQjH GdaYGd (B/s - (3GdNGWQ, aGjRs ((3YeGf(B: s (3OGQ GSGeI(B, s, 2010)
(3eGgjI GdJOQjH , JUeje GdJOQjH GdaYGd , CSGdjH h WQb GdJOQjH GdaYGd , GdJWhjQ h GdJZjjQ h GdJOQjH , ESJQGJjLjI GdJOQjH GdaYGd , JMOjO GdGMJjGLGJ GdJOQjHjI , fXQjGJ GdJYdje h GdJOQjH , JMhjd GdJOQjH , GdGSJQGJjLjI GdJfXjejI h ESJQGJjLjI JfejI h JWhjQ GdYGedjf , JWhjQ GdehXajf , JUeje GdJbjje GdJOQjHj , eSJbHd GdJOQjH h GdJWhjQ(B.s
(3eQGLY (B: (3dcd aUd eQLY ; bGFeI GdeQGLY U(B.221s
Keywords: (3EOGQI GdGaQGOs; (3GSJQGJjLjI GdJOQjHs; (3GdGOGQI GdYGeIs; (3JOQjH GdehXajfs